Blindsided by the American Dream - Lisella, Maria (Italian Canadiana)

(untitled) (Iter Press, 2020)
In her essay “Shades, Color and Internal Dialogues in White America,” from which the present contribution is taken, Maria Lisella takes a savvy streetwise approach to balancing feminism with political consciousness. By sifting through the nuances and politics of her own body language in what appears to be a moment of imminent danger, she takes the long view by educating herself. She achieves this through listening to others’ individual experiences some of which depict white liberals trapped in a web of well-meaning gestures that can endanger them. From the human stories behind racism and prejudice in the Italian American community, she illustrates that dogmatic formulas do not address all situations; understanding among races can only be achieved through direct interaction with each other.